Revealing Employer’s Name in Social Networks - Sander Tom; Pūķe Ieva; Sloka Biruta (Economics and Business)
The research investigates the question of the importance of mentioning the name of the employer in online and offline social networks. The exchange of information is an important part of social networks and social capital theory. Companies can use the networks of their employees to recruit new hires and to check habits and interests of likely new employees. To do that, the employee has to mention the name of the company in these social networks. The paper compares different real social networks used by family and friends and private and business social network sites (SNSs) as online social networks and compares the differences between men and women. The empirical research has been done by a survey. The survey data are analysed using the main indicators of descriptive statistics, frequency, t-test and cross tables. The results of the research reveal that real social networks are more accepted than virtual social networks. The difference in use of social networks between genders is confirmed.